Nilai-nilai Karakter dalam Serat Wira Wiyata dan Kesesuaiannya dalam Pembelajaran Bahasa Jawa Tingkat SMK - Heru, Azis; Nurhayati, Endang; Venny Indria Ekowati (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This research is based on the study of Javanese manuscripts. This research contains two objectives. The first objective of this study is to explain the character values in Serat Wira Wiyata. The second objective of this research is to describe the suitability of character values in Serat Wira Wiyata in Javanese language learning at the Vocational School level. The results of this study explain two things. The first is the character values in Serat Wira Wiyata. The character values found in Serat Wira Wiyata are religiosity, discipline, hard work creativity, responsibility, and affection. Three-character values are characteristic of Serat Wira Wiyata, namely the character values of being wise, obedient, and brave. The result of the second study is to explain the suitability of the character values in the Serat Wira Wiyata for learning Javanese. Based on the results of the adjustments to the 2013 curriculum, these character values are still appropriate to be applied in learning Javanese at the Vocational School level.